GRAMMAR: IS IT ESSENTIAL TO TEACH IT EXPLICITLY AT SECONDARY SCHOOLS ? - Amri Isyam (Proceedings of ISELT FBS Universitas Negeri Padang, 2013)
The article aims at discussing whether English grammar has to be taught at secondary schools in Indonesia. Internationally, whether grammar has to be taught has been controversial issues in second/foreign language teaching (SLT/FLT) at least for the last two decades. A few extremists have advocated that teaching grammar is not needed at all while a lot of language educators support the teaching of grammar. Some experts state that historically grammar has become central in SLT/FLT. Even one of them surprisingly claims that grammar is so important that she regards it as the fifth skill named grammaring after the other four: listening, speaking, reading, and writing skills. In fact, the writer agrees to say that grammar is one of the skills that learners must acquire in learning English as a foreign language (EFL). However, it is not the fifth. It must become the first because EFL learners will not understand well what they are listening to or reading, or they will not be able to speak or write well in English without understanding or mastering its grammar first. Hence, grammar cannot be neglected in ELT at secondary schools in Indonesia. It must be taught explicitly, and there should be some specially-allocated time to teach it.